Analisis Tingkat Kesehatan dan Ukuran Perusahaan Terhadap Pertumbuhan Laba Bank Umum Syariah di Indonesia - Qothrunnada, Qothrunnada; Wardana, Guntur Kusuma (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2021)
The purpose of the study was to determine the effect of the level of soundness and company size partially and simultaneously on the profit growth of Islamic Commercial Banks in Indonesia in 2016-2020. The population in the study was 14 Islamic Commercial Banks in Indonesia in 2016-2020 which were registered with the Financial Services Authority (OJK), using a purposive sampling technique there were 12 banks that became the research sample. The analytical method used is multiple linear regression analysis using Eviews10. The results show that Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), Good Corporate Governance (GCG), Capital Adequacy Ratio (CAR), and company size partially have no significant effect on profit growth at Islamic Commercial Banks in Indonesia. the 2016-2020 period, while the Return on Assets (ROA) partially has a significant effect on profit growth. Simultaneously Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Good Corporate Governance (GCG), Return On Assets (ROA), Capital Adequacy Ratio (CAR), and company size have a significant effect on profit growth. Keywords: Health Level, Company Size, and Profit Growth